Molecular characterization of chalcone isomerase (CHI) regulating flower color in herbaceous peony (Paeonia lactiflora Pall.) - Yan-qing WU; Meng-yuan ZHU; Yu JIANG; Da-qiu ZHAO; Jun TAO (Journal of Integrative Agriculture, 2018)
Chalcone isomerase (CHI) is a key enzyme that converts yellow chalcone to colorless naringenin, playing an important regulatory role in color formation of ornamental flowers. We determined the coding sequence of CHI in herbaceous peony using rapid-amplification of cDNA ends (RACE) technology, and subsequently detected the expression pattern of CHI in the inner and outer petals at different developmental stages using qRT-PCR. We cloned the upstream promoter sequences of CHI using genome walking technology and predicted the location of CpG islands and 5′ truncation. In addition, we constructed five dual-luciferase reporter gene carriers and detected the promoter activities of different fragments. Our results showed that the full-length cDNA sequence of CHI was 898 bp, and the 5′-upstream core promoter was located at −1651 to −2050 bp region, where contained one CpG island (−1897 to −2010 bp) and several important binding sites of transcription factor, such as Sp1, serum response factor (SRF), activating protein (AP)-2alpha and CCAAT/enhancer binding protein (C/EBP)alpha. Expression results showed that the expression of CHI at different developmental stages was generally higher in inner petals than those in outer petals, and the maximum at the bud stage (S1). Thus, this study will provide theoretical basis for an in-depth study of CHI gene function and expression regulation.